Lumbar neuraxial anatomical changes throughout pregnancy: a longitudinal study using serial ultrasound scans. (4th February 2016) - Keplinger, M.; Marhofer, P.; Eppel, W.; Macholz, F.; Hachemian, N.; Karmakar, M. K.; Marhofer, D.; Klug, W.; Kettner, S. C.
Summary: This observational study was designed to investigate the anatomical changes of the lumbar spine over the course of pregnancy using serial ultrasound scans. We performed paramedian scans on 58 women at the L2–3, L3–4 and L4–5 levels; these were done at four periods of 11+0–13+6, 19+0–23+0, 28+0–32+0 and 38+0–40+0 weeks gestation. At each intervertebral level, the length of the interlaminar space, length of the visible intervertebral posterior dura and depth of the posterior dura mater from the skin were measured. The length of the interlaminar space and length of the visible intervertebral posterior dura mater were longer, and the depth of the posterior dura mater was shallower, with ascending spinal interspace. The depth of the posterior dura mater increased during pregnancy, although it plateaued between the third and fourth measurement periods. The other spinal measurements were not affected by gestation. These findings indicate that the L2–3 level is the most appropriate puncture site for epidural anaesthesia in pregnant women. Our results ought to be embraced as a departure point towards developing neuraxial insertion techniques guided or aided by ultrasound.